Assessment of Health and Quality of Life of Children Residing in Selected Shelter Homes in Bangalore - Jacquline Elza Johnson, Prathap Raja Varma MAN, Eswaran Maheswari, Saraswathy GR (Journal of Applied Pharmaceutical Science, 2018)
Objectives: Children needs diligent fostering to shape the future of a nation. The study was undertaken to analyze the health and quality of life (QoL) of children in selected shelter homes in Bangalore. Materials and Methods: It is a community-based study conducted in three shelter homes among 108 children. Health was assessed using a suitably designed form. QoL was measured using WHOQOL-BREF questionnaire. Results: In the study, 73 (67.59%) had below normal nutritional status. 50 (54%) had an abnormal vision, 4 (3.7%) had impaired muscle and tendon reflex. Dental caries was observed in 40 (37%) children. Tinea versicolor was observed in 21 (19.4%) children. Scabies was observed in 7 (6.48%) children. QoL was found to be highest in an environmental domain with 44.4%, followed by 43.5% in psychological domain, 37% in the physical health and 14.8% in the social relationship domain. Conclusion: The study revealed that children have health problems and low QoL. In India, health problems and low QoL among shelter home children are increasing which needs better health care policies to support the organizations before they collapse under the burden of health care issues.
Keywords: Children, Shelter homes,Quality of life, Malnutrition.